(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The article analyzes and studies the experience of foreign countries in assessing the financial stability of commercial banks. In particular, the advanced foreign experience of the USA, Germany, France, Italy, and the Russian Federation in this regard, as well as the opinions and comments of economists, are analyzed.